The interrelationship between policemen’s coping strategies and features of emotional intelligence - Chung, M.C.; Sabirova, R.Sh.; Umurkulova, M.M. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The urgency of the problem considered in the article is the insufficient illumination in the domestic psychological literature of the issues of coping behavior in the context of connection with emotional intelligence. Emotional intelligence is understood as the ability to understand emotions, manage them, build adequate interpersonal relationships. The author gave the analysis of the concepts of «coping», «stress-overcoming behavior», «strategy of coping behavior». In the course of theoretical and empirical study patterns of formation and functioning of stress-overcoming behavior were identified, the relationship between coping and the specifics of the components of emotional intelligence was indicated. A qualitative characteristic of coping was given, which combines the important indicators of personal competence and the success of interaction in professional activities; the relationship between coping behavior and emotional intelligence of law enforcement officers in terms of a systematic approach was determined. The relationship of psychological conditions for the success of social adaptation through the system of coping behavior is considered. It is proved that stress-overcoming behavior is one of the important psychological factors for ensuring the effectiveness of professional activity in extreme conditions. It is revealed that the structure and content of strategies of overcoming behavior are under the determining influence of the abilities and skills that form the emotional intelligence of the individual. Social adaptation of individuals with highly developed emotional intelligence is a complex personality trait that relies primarily on the ability to control one’s own emotions, to motivate oneself to master the skills of emotionally saturated and regulated behavior, to recognize the emotions of other people, and generally to highly developed emotional intelligence as integral personal ability. Persons with high coping potential are endowed with great opportunities for social and psychological adaptation in various conditions of activity.
Полиция қызметкерлерінің копинг-стратегиялары мен эмоциялық зерде ерекшеліктері арасындағы байланыс
Взаимосвязь копинг–стратегий и особенностей эмоционального интеллекта у сотрудников полиции
Keywords: stress; coping strategy; stress-overcoming behavior; emotional intelligence; coping behavior